Resistance to Early-Life Stress in Mice: Effects of Genetic Background and Stress Duration - Savignac, Helene M.; Dinan, Timothy G.; Cryan, John F. (Frontiers in Behavioral Neuroscience, 2011)
Early-life stress can induce marked behavioural and physiological impairments in adulthood including cognitive deficits, depression, anxiety and gastrointestinal dysfunction. Although robust rat models of early-life stress exist there are few established effective paradigms in the mouse. Genetic background and protocol parameters used are two critical variables in such model development. Thus we investigated the impact of two different early-life stress protocols in two commonly used inbred mouse strains. C57BL/6 and innately anxious BALB/c male mice were maternally deprived 3 hrs daily, either from postnatal day 1 to 14 (Protocol 1) or 6 to 10 (Protocol 2). Animals were assessed in adulthood for cognitive performance (spontaneous alternation behaviour test), anxiety (open field, light/dark box and elevated plus maze tests) and depression-related behaviours (forced swim test) in addition to stress-sensitive physiological changes. Overall, the results showed that early-life stressed mice from both strains displayed good cognitive ability and no elevations in anxiety. However, paradoxical changes occurred in C57BL/6 mice as the longer protocol (protocol 1) decreased anxiety in the light-dark box and increased exploration in the elevated plus maze. In BALB/c mice there were also limited effects of maternal separation with both separation protocols inducing reductions in stress-induced defecation and protocol 1 reducing the colon length. These data suggest that, independent of stress duration, mice from both strains were on the whole resilient to the maladaptive effects of early-life stress. Thus maternal-separation models of brain-gut axis dysfunction should rely on either different stressor protocols or other strains of mice.